1997
DOI: 10.1161/01.cir.96.12.4204
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Influence of Increased Fibrinogen and C-Reactive Protein Levels in Unstable Coronary Artery Disease

Abstract: Increased levels of both fibrinogen and C-reactive protein are associated with a worse outcome in patients with unstable coronary artery disease. The increased risk associated with elevated fibrinogen levels is independent of, and additive to, the prognostic influence of myocardial damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
247
0
14

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 469 publications
(270 citation statements)
references
References 29 publications
9
247
0
14
Order By: Relevance
“…11 It has been demonstrated that CRP increases in acute coronary syndromes (unstable angina and AMI) and that it is associated with an adverse outcome regarding both short and long term prognosis. 21,22 It has been reported that increased serum CRP level was associated with a greater increase in LV volume after acute anterior MI. 23 Also CRP is a risk factor for LV thrombus and cardiac rupture after MI.…”
Section: Discussionmentioning
confidence: 99%
“…11 It has been demonstrated that CRP increases in acute coronary syndromes (unstable angina and AMI) and that it is associated with an adverse outcome regarding both short and long term prognosis. 21,22 It has been reported that increased serum CRP level was associated with a greater increase in LV volume after acute anterior MI. 23 Also CRP is a risk factor for LV thrombus and cardiac rupture after MI.…”
Section: Discussionmentioning
confidence: 99%
“…It takes part in the atherosclerosis process inducing plaque growth, stimulating adhesion of platelets and white blood cells to the vessels wall cells, endothelial dysfunction, and promoting muscle cell proliferation and migration [9,10]. Plasma fibrinogen levels have been found to be higher in patients with ACS compared to those of patients with stable coronary artery disease or healthy controls, and higher plasma fibrinogen levels may be predictors of poor long-term prognosis [11][12][13][14]. The association of the extent and complexity of atherosclerosis in ACS with fibrinogen levels has not been adequately studied.…”
Section: Introductionmentioning
confidence: 99%
“…There is increased recognition that inflammation plays a key role in the pathogenesis and outcome of ACSs (3). Previous studies have constantly shown that high circulating levels of C-reactive protein (CRP) incur an increased risk of long-term cardiovascular mortality in patients with either ST-segment elevation MI (STEMI) (4-7), or non-ST-segment elevation ACSs (NSTE-ACS) (7)(8)(9)(10)(11). Elevated concentrations of CRP can also be found in subjects with ACS.…”
Section: Introductionmentioning
confidence: 99%